Work-Life Balance For Policewomen: The Role of Co-Worker Support and Work Flexibility - Nur Syerlai Santosa; Trubus Raharjo (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Study This done For study relatedness between support colleague work and flexibility Work to Work-life balance member police woman. Approach quantitative used in study with subject of policewomen at Kudus Police. Population study covers all over female police officers, while technique accidental sampling used For determine sample as many as 60 respondents. A total of 37 data were stated fulfil assumptions normality. Instrument data collection consists of on scale work life balance , support colleague work , and flexibility Work with mark reliability of 0.950; 0.953; and 0.934, respectively. The data were analyzed use approach regression with two variables predictor as well as testing correlation product moment, with help device SPSS software. Research results indicates that there is very strong relationship between support colleague work and flexibility Work with Work-life balance that is r = 0.787 and p < 0.01 contribute effective 61.9%. In general partial , support colleague Work r = 0.701 with p < 0.01, and flexibility Work r = 0.765 and r < 0.01 also shows connection proven positive​ real to balance life work (work-life balance). Findings in study This indicate the more increase it support colleague work and flexibility Work so become the more good level too from work life balance in policewomen.